PENGEMBANGAN MEDIA LEAFLET DIGITAL MENGENAI PENCEGAHAN DIABETES MELITUS TIPE 2 DI SMAN 1 SURADE KABUPATEN SUKABUMI - Putri Ghina Nabilah; M.Aris Rizqi (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Diabetes mellitus in Indonesia Based on open 2data, West Java, the number of diabetes sufferers in Sukabumi district in 2019 was 148,447. Meanwhile, in the Ciracap area there were 330 cases out of a total population of 47,495 people. This is due to a lifestyle of lack of physical activity, as well as a lack of information on preventing type 2 diabetes mellitus as an educational medium. Because digital leaflet media is needed that is not boring to make it easier to provide health education regarding the prevention of type 2 diabetes mellitus in the era of digitalization. Objective: To produce digital leaflet media regarding the prevention of type 2 diabetes mellitus in adolescents. Method: Development uses a 4D model selected based on simple random sampling techniques and data collection is carried out by in-depth interviews with data collection methods, namely media feasibility test questionnaires and data analysis using the feasibility percentage formula. Results: Qualitative research at the Define and design stage was carried out using in-depth interviews, including that the media content had to be informative, the language and design of the digital leaflet attractive. Quantitative research at the Development and Dissemination stage showed that the feasibility test results from material experts were 93.2%, media experts were 97% and teenagers were 91%, meaning that the media was